Manuscript Works of Sheikh Marfi Nodei in Iranian Libraries – A Statistical Descriptive Study (Sulaimani Journal for Humanities, 2024)
Sayyid Mohammed son of Sayyid Mustafa Barzanji, also known as Sheikh Marfi Nodei, was one of the greatest Kurdish scholars of the thirteenth century AH. During his lifetime, he was able to create many works in various scientific fields. Until recently, some of his works have been used as source books in Kurdistan's rooms, and many of his works have been copied dozens of times. The increase in the number of his scientific works and the availability of many manuscripts of them clearly shows the influence and importance of Sheikh Marf's personality and writings on scholars after him. A large number of his manuscripts are currently preserved in libraries around the world. Iranian libraries are not without Sheikh Marf's manuscripts. In this paper, we try to introduce Sheikh Marf's manuscript works in Iranian libraries in an analytical manner using statistical data. In addition, we will correct with evidence any errors that have occurred in recording the name of the work, the date of writing, the name of the author or copyist in the list of manuscripts in these libraries - causing these manuscripts to remain hidden. Some of the results indicate that a total of 61 manuscripts of 19 works of Sheikh Marf are preserved in Iranian libraries. This figure is divided into 16 libraries in seven major Iranian provinces. More details are provided in the text of this article.
Keywords: Sheikh Marf; Sheikh Marfi Nodei; Manuscripts of Sheikh Marfi Nodei; Manuscripts of Iranian Libraries